State versus tribal borders: Problems of irredentism in modern Libyan state-building process [version 1; peer review: 2 approved] - Rawia Ben Khayal (Routledge Open Research)
This article sets out to examine the tensions that exist in post-Gaddafi Libya with respect to the establishment of central government and one of the sub-state actors, namely tribes. The study finds that, as a result of its colonial past, Libya as a state was created by negotiations between British, French and Italian colonial powers without regard to the indigenous populations such as the North African tribes with their natural tribal heartlands. This has led to an incoherence between identity and territory and in turn has created problems of irredentism and national security issues. After a detailed examination of Libya’s extensive East, West and Southern borders, the article finds that as a state, Libya is unable to control its borders and so cannot qualify as a fully functioning nation-state according to Western definitions of the phenomenon. The article then discusses the complex issue of the differences between state-building and nationhood and finds that according to the definitions of the 14th century Maghreb sociologist Ibn Khaldun, while the state and the nation are two different concepts, one cannot exist without the other. This stands in contrast to the modern, global emphasis on linear as opposed to cyclical development and reflects the values of donor states and not the complex needs of emerging and fragile democratic states. The article therefore recommends the need for understanding, trust and compromise from all parties involved. For example, while tribes contribute the much-needed values of nationhood, they must in turn respect the values of democracy such as the rule of law. Conversely, external players should respect the concept of national identity with its emphasis on the value of social cohesion.